ANALISIS KREATIVITAS SISWA YANG SUKA BERMAIN PS (PLAY STATION)DI SDN 010 BAGAN NIBUNG KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR T. P.2013 / 2014 - Yusuf, Sardi Yusuf Sardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Based on observationsby the authorthroughinterviewsandquestionnaires, most studentshave the creativityplayful PS. The purposeof thisstudyis: 1). Toknow the description ofstudent creativitythatloves to playPSin the aspect ofcurrentthinking. 2). Toknow the description ofstudent creativitythatloves to playPSinflexiblethinkingaspect. 3). Toknow the description ofstudent creativitythatloves to playPSindetail aspects. 4). Todetermine the imagecreativityPSstudents wholike to playin this aspect ofrational thinking. 5). Toknow the description ofstudent creativitythatloves to playPSinassessingaspects. 6). Toknow the description ofstudent creativitythatloves to playPSinaspectscuriosity. 7). Tofind a picture of student creativitythatloves to playPSinnatureimaginativeaspect. 8). Toknow the description ofstudent creativitythatloves to playPSinaspectschallengedbyprogress. 9). Tofind a picture of thestudents' creativityplayfulaspectPsinrisk-taking. 10). Toknow the description ofstudent creativitythatloves to playPSinaspect to appreciatenature.Inthisstudyused descriptivequantitativeapproach. The populationin this study werestudents of classIV, V, andVISDN010BaganNibungSimpangKananacademic year2013/2014, amounting to 80studentsand the sampleasa populationthat is 80studentsand theuseof saturatedsamples(total sampling) thatall populationsamples. Based on the resultsof dataprocessing, the creativityof studentswholike to playPS(PlayStation) review of aspects ofcurrentthinkingskillsareclassifiedintocategories, namely: 75%, studentwhen viewed from theaspect offlexiblethinkingskillsareclassifiedintocategories, namely: 77.5%, studentswhen viewed fromthe aspectrefineskillsfall intothe category of being, namely: 73.75%, the studentswhen viewed from theaspect ofrational thinkingskills areclassifiedintocategoriesasfollows:62.5% of students when viewed from theaspect ofassessingskillsareclassifiedintocategories, namely: 77,5%, if thestudentsin termsofcuriosityclassified in the categoryareas follows:73.75%, if thestudentisimaginativein terms of aspectsareclassifiedincategories, namely: 81.25%, when viewed from thestudentsfeel challengedbyadvancesclassifiedincategoriesareas follows:73.75%, the studentswhen viewed from theaspect ofthe nature ofrisk-takingclassified in the categoryareas follows:73.75%, the studentswhen viewed from theaspect ofnatureappreciateclassified in the categoryareas follows:77.5%. Keyword: problems, teenagers,creativity.